The Systolic Pulmonary Arterial Pressure Liaises Impaired Cardiac Autonomic Control to Pro-inflammatory Status in Systemic Sclerosis Patients - Rodrigues, Gabriel D.; Vicenzi, Marco; Bellocchi, Chiara; Beretta, Lorenzo; Carandina, Angelica; Tobaldini, Eleonora; Carugo, Stefano; Montano, Nicola (Frontiers in Cardiovascular Medicine, 2022)
The current study was undertaken to test the hypothesis that systemic sclerosis (SSc) patients with higher systolic pulmonary arterial pressures (PAPs) present a blunted cardiac autonomic modulation and a pro-inflammatory profile. Thirty-nine SSc patients were enrolled (mean age 57 ± 11 years). ECG and respiration were recorded in the supine (SUP) position and during the active standing (ORT). Heart rate variability (HRV) analysis was performed on samples of 300 beats. The symbolic analysis identified three patterns, 0V%, (sympathetic) and 2UV% and 2LV%, (vagal). The %ΔORT was calculated from the differences between HRV in ORT and SUP, normalized (%) by the HRV values at rest. The PAPs was obtained non-invasively through echocardiography. For the inter-group analysis, participants were allocated in groups with higher (+PAPs ≥ median) and lower PAPs (–PAPs < median) values. At rest, the cardiac sympathetic modulation (represented by 0V%) was positively correlated with PAPs, while parasympathetic modulation (represented by 2LV%) was negatively correlated with PAPs. The dynamic response to ORT (represented by Δ0V% and Δ2LV%), sympathetic and parasympathetic were negatively and positively correlated with PAPs, respectively. The +PAPs group presented a higher inflammatory status and a blunted cardiac autonomic response to ORT (↓Δ0V% and ↑Δ2LV%) compared to the –PAPs group. These findings suggest an interplay among cardiac autonomic control, inflammatory status, and cardiopulmonary mechanics that should be considered for the assessment, monitoring, and treatment of SSc patients.